Quantitative easing, uncertainty, and risk aversion - Rompolis, Leonidas S. (Journal of Banking & Finance, 2025)
This study examines the impact of European Central Bank (ECB) monetary policy surprises on economic uncertainty and investor risk aversion. We identify four factors using a high-frequency event-study approach. These factors measure surprises regarding the current setting of policy rates (Target), the bank’s future policy path (Forward Guidance), and quantitative easing (QE). The fourth factor reflects unexpected news about future macroeconomic conditions. Our main finding is that quantitative tightening surprises, proxied by positive QE surprises, increase economic uncertainty and investor risk aversion. Additionally, we document the significant response of key macroeconomic variables to these surprises.